2004
DOI: 10.1212/01.wnl.0000110185.23464.a1
|View full text |Cite
|
Sign up to set email alerts
|

How long is IVIg effective in multifocal motor neuropathy?

Abstract: The authors treated 10 patients with multifocal motor neuropathy (MMN) responding to an initial course of IV immunoglobulin (IVIg) with periodic infusion for 5 to 12 years (mean 8.2 years). At last follow-up, only two patients had maintained the maximal improvement achieved during therapy while eight worsened despite increasing Ig dosage. This decline started after 3 to 7 years (mean 4.8 years) of therapy and correlated with a reduction of distal compound muscle action potential amplitudes (p < 0.019). The eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
98
1
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 9 publications
10
98
1
7
Order By: Relevance
“…It is notable that dosing remained constant or was only slightly changed in the majority of patients over the course of 1 year. Notably, authors of a retrospective study found reliably good shortterm response to IVIG, but declining effectiveness in long-term follow up of patients [Léger et al 2008], that was confirmed by other studies [Van Den BergVos et al 2002;Terenghi et al 2004], while in another study their IgG effectiveness persisted [Vucic et al 2004]. In our study, IgG treatment was stopped in only one patient who did not have a clinical benefit from the treatment.…”
Section: Treatmentsupporting
confidence: 88%
“…It is notable that dosing remained constant or was only slightly changed in the majority of patients over the course of 1 year. Notably, authors of a retrospective study found reliably good shortterm response to IVIG, but declining effectiveness in long-term follow up of patients [Léger et al 2008], that was confirmed by other studies [Van Den BergVos et al 2002;Terenghi et al 2004], while in another study their IgG effectiveness persisted [Vucic et al 2004]. In our study, IgG treatment was stopped in only one patient who did not have a clinical benefit from the treatment.…”
Section: Treatmentsupporting
confidence: 88%
“…The authors concluded that IVIG maintenance therapy had a beneficial long-term effect on muscle strength and upper limb disability but may not prevent a slight decrease in muscle strength. Similar results were found by other authors who reported follow-up in 10 patients with MMN responding to an initial course of IVIg with periodic infusion for 5-12 years (mean 8.2 years) [80]. At the last follow-up, only 2 patients had maintained the maximal improvement achieved during therapy, while 8 worsened despite the immunoglobulin dosage.…”
Section: Ivigsupporting
confidence: 89%
“…The authors concluded that IVIg maintenance therapy has a beneficial long-term effect on muscle strength and upper limb disability but may not prevent a slight decrease in muscle strength, and that IVIg treatment favourably influences the mechanisms of remyelination or reinnervation but that axon loss cannot be prevented. Same data and conclusions were outlined by Terenghi et al [37] 10 patients with multifocal motor neuropathy responding to an initial course of IVIg with periodic infusion for 5 to 12 years (mean 8.2 years). At last follow-up only 2 patients had maintained the maximal improvement achieved during therapy, while 8 worsened despite increasing IVIg dosage.…”
Section: Ivig In the Long-term Treatment Of Multifocal Motor Neuropathymentioning
confidence: 53%